Association Between Different Indicators of Obesity and Depression in Adults in Qingdao, China: A Cross-Sectional Study - Cui, Jing; Sun, Xiufen; Li, Xiaojing; Ke, Ma; Sun, Jianping; Yasmeen, Nafeesa; Khan, Jamal Muhammad; Xin, Hualei; Xue, Shouyong; Baloch, Zulqarnain (Frontiers in Endocrinology, 2018)
Background: This study was designed to investigate the perceived relationship between body weight and depression risk in a Chinese population in Qingdao, China. Methods: A population-based cross-sectional survey was performed with 4,573 participants (between 35 and 74 years) from the year 2009 to 2012 in Qingdao, China. We applied the Zung self-rating depression scale to ascertain the level of depression in participants. The associations between different indicators of obesity [body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR)] and depression were assessed by logistic regression based on the Chinese criteria of obesity. Sensitivity analysis was done based on the Asian and WHO criteria of obesity. Results: The Zung scores for the 243 participants (5.2%) were over 45 and they were entitled as depression. Furthermore, multivariable logistic analyses revealed that being overweight [odds ratios (OR): 1.48, 95% confidence intervals [95% CI]: 1.08–2.03] and having abdominal obesity (WC category in Chinese criteria) (OR: 1.47, 95% CI: 1.08-2.00) were often associated with a higher risk for depression compared to normal weight subjects. Sensitivity analysis revealed that abdominal obesity (Asian criterion) (OR: 1.41, 95% CI: 1.03-1.91) was a significant risk factor for depression. Similarly, being overweight (WHO criterion) (OR: 1.39, 95% CI: 1.03-1.87) was an obvious risk factor for depression. Conclusion: Being overweight and having abdominal obesity (WC category) were found to be linked with a higher risk of depression. However, abdominal obesity (WHR category) was not associated with depression.